Colletteichthys occidentalis, a new Toadfish Species from the Arabian Peninsula and Northern Arabian Sea (Teleostei: Batrachoididae) - Greenfield, David W. (Zootaxa, 2012)
The second known species in the genus Colletteichthys is described from the Arabian Peninsula and the northern ArabianSea, supporting the validity of the genus Colletteichthys. Compared to the other known species, C. dussumieri from India,C. occidentalis has only a single tentacle above the eye whereas C. dussumieri has two or more. Colletteichtyhs dussumieri is restricted to the west coast of India.